2009
DOI: 10.1111/j.1551-6709.2009.01027.x
|View full text |Cite
|
Sign up to set email alerts
|

The Wind Chilled the Spectators, but the Wine Just Chilled: Sense, Structure, and Sentence Comprehension

Abstract: Anticipation plays a role in language comprehension. In this article, we explore the extent to which verb sense influences expectations about upcoming structure. We focus on change of state verbs like shatter, which have different senses that are expressed in either transitive or intransitive structures, depending on the sense that is used. In two experiments we influence the interpretation of verb sense by manipulating the thematic fit of the grammatical subject as cause or affected entity for the verb, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 39 publications
(54 reference statements)
4
43
0
Order By: Relevance
“…A similar demonstration of the use of meaning to predict structure is reported in Hare et al (in press). That study examined expectancies that arise during incremental processing of sentences that involve verbs such as collect , which can occur in either a transitive construction (e.g., The children collected dead leaves , in which the verb has a causative meaning) or an intransitive construction (e.g., The rainwater collected in the damp playground , in which the verb is inchoative).…”
Section: Arguments For An Enriched Lexiconmentioning
confidence: 80%
See 1 more Smart Citation
“…A similar demonstration of the use of meaning to predict structure is reported in Hare et al (in press). That study examined expectancies that arise during incremental processing of sentences that involve verbs such as collect , which can occur in either a transitive construction (e.g., The children collected dead leaves , in which the verb has a causative meaning) or an intransitive construction (e.g., The rainwater collected in the damp playground , in which the verb is inchoative).…”
Section: Arguments For An Enriched Lexiconmentioning
confidence: 80%
“…Thus, sometimes the ambiguity was resolved in a way that did not match participants’ predicted expectations. The data (reviewed in more detail in Hare, Elman, Tabaczynski, & McRae, in press) suggest that comprehenders’ expectancies regarding the subcategorization frame in which a verb occurs is indeed sensitive to statistical patterns of usage that are associated not with the verb in general, but with the sense-specific usage of the verb. A computational model of these effects is described in Elman et al (2005).…”
Section: Arguments For An Enriched Lexiconmentioning
confidence: 99%
“…Kako (2006) showed in a series of studies that readers given noun-verb-noun strings (where the nouns were actually nonsense words) consistently assigned more agent properties to the preverbal word, and more patient properties to the post-verbal one. Work in sentence processing has also shown that comprehenders anticipate specific roles based on the structural properties of the verb (Hare, Elman, Tabaczynski, & McRae, in press; Tanenhaus, Carlson, & Trueswell, 1989), and so would anticipate a patient, not an instrument, immediately following chopped . The lumberjack chopped the axe example thus shows that the discourse representation includes information about roles in the event, and when the participant does not fit the structurally-defined role, or fits some other role, there is no facilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to Laszlo and Federmeier (2009), Kim and Lai argued that 2 Within-category words were never lexical associates of the target words, but association norms include only strongly semantically related items. Importantly, lexical priming can also occur from semantically related or lexically co-occurring words which are non-associated (e.g., Hare, Elman, Tabaczynski, & McRae, 2009). the impact of prediction occurs before visual word recognition (because pseudowords cannot be recognized as words).…”
Section: Predicting Formmentioning
confidence: 99%